An economic analysis of government expenditure allocations to black schooling in South Africa - Hosking, Stephen Gerald (Rhodes University, Faculty of Commerce, Department of Economics, 1991)
In this thesis an assessment is made of the contribution of economic theory to the debate on government expenditure allocations to schooling in developing countries. Publicly provided Black schooling in South Africa is taken as the case study and viewed in the light of historical perspectives, as well as human capital, rent-seeking, welfare, liberal and contractarian theory. From an historical perspective, the willingness of Blacks to enrol at schools under National Party control, despite the poor quality of such schooling and lack of labour market incentives for them to do so, is paradoxical. It leads to the conclusion that under National Party administration the private benefit of Black schooling exceeded the private cost; a situation which is argued to have been influenced by rent-seeking. The propositions that government expenditure on Black schooling is a profitable social investment, and that rent-seeking has influenced the allocations of government expenditure on Black and White education are then investigated. Empirical support is found for both propositions, but it is based on the use of controversial methods and measures. The provision of education by the state can be justified on many economic grounds; the most popular being that this improves welfare by bringing about a better distribution of income or by redressing market failure. However, as there are major problems with this approach, it is concluded that neoclassical welfare theory fails to provide a persuasive justification for current levels of government expenditure on Black schooling. The provision of Black schooling by the state can also be justified in terms of liberal objectives. Classical and reform liberalism and their respective conclusions are examined. Marxist views on the role played by the state in the provision of education are also considered, but not found to be appropriate. Two contractarian assessments of the government's role in the provision of Black schooling are also provided in this thesis. They are based on the works of John Rawls (1971 and 1974) and James Buchanan (1986). The approach taken by James Buchanan is argued to be more appropriate to South African circumstances than Rawls's, and it is in the context of the former that problems with respect to public decisions on education and possible solutions to them are discussed. The conclusion of the thesis is that economic theory offers only a limited explanation for government expenditure allocations to Black education in South Africa
Keywords: Black people -- Education -- Economic aspects -- South Africa; Education -- Economic aspects -- South Africa; Education and state -- South Africa; Education -- Finance -- South Africa